2018
DOI: 10.5194/acp-18-15687-2018
|View full text |Cite
|
Sign up to set email alerts
|

Particle number size distribution and new particle formation under the influence of biomass burning at a high altitude background site at Mt. Yulong (3410 m), China

Abstract: Abstract. Biomass burning (BB) activities have a great impact on the particle number size distribution (PNSD) in the upper troposphere of the Tibetan Plateau, which could affect regional and global climate. An intensive campaign focused on the measurement of the PNSD, gaseous pollutants, and meteorological parameters was conducted at Mt. Yulong, a high-altitude site (3410 m a.s.l.) on the southeastern Tibetan Plateau during the pre-monsoon season (22 March to 15 April). During this period, intensive BB activit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 71 publications
12
33
1
Order By: Relevance
“…Heng (Nie et al, 2014), Mount Waliguan (Kivekas et al, 2009), and Mt. Yulong (Shang et al, 2018). Lv et al (2018) conducted observations during the different seasons in 2004 and 2005 at the summit of Mt.…”
Section: Npf At High Elevationmentioning
confidence: 99%
“…Heng (Nie et al, 2014), Mount Waliguan (Kivekas et al, 2009), and Mt. Yulong (Shang et al, 2018). Lv et al (2018) conducted observations during the different seasons in 2004 and 2005 at the summit of Mt.…”
Section: Npf At High Elevationmentioning
confidence: 99%
“…Atmospheric particles influence the earth's energy balance by directly interacting with the solar radiation and indirectly being activated as cloud condensation nucleation (CCN) (Ghan and Schwartz, 2007). New particle formation (NPF) in the atmosphere and the coagulation herein may enable particles to grow larger than 60 nm, at which point aerosols can exert radiative effects on the solar radiation and act as CCN (Williamson et al, 2019;Shang et al, 2021). Some researchers find that the NPF is responsible for around half of the global CCN (Merikanto et al, 2009;Du et al, 2017;Kulmala et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…G. Zhao et al: Impact of aerosol-radiation interaction on new particle formation (CS) (Kulmala et al, 2001;Shang et al, 2021). The [OH] is related to solar ultraviolet radiation (Rohrer and Berresheim, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It can be reflected by the high pollutant concentration during the daytime due to the strong convective mixing. In a previous publication based on the same measurement, Shang et al (2018) found an increasing trend of Aitken-mode particle number concentration during the daytime. By examining the available evidence, they believed that those Aitken-mode particles came 190 from the primary emissions under the mountain.…”
Section: Observational Evidence For the Transport Of Biomass Burning mentioning
confidence: 57%